Immunomodulatory properties of plants of the genus Filipendula - E. V. Sokolova; D. N. Baleev (Овощи России, 2023)
This paper analyzes the literature data on the practical use of plants of the genus Filipendula as a nutritional component and a promising source of biologically active substances. For immunomodulatory action, the flowers and leaves of the meadowsweet are mainly used, which have demonstrated a significant effect in numerous in vitro and in vivo models. Among the diseases in which the immunomodulatory properties of plants of the genus Filipendula are found the most application are inflammatory processes of the upper respiratory tract, a number of inflammatory disorders of the skin, as well as a diaphoretic and antispasmodic, in bronchial asthma, etc. An analysis of the literature data allows us to conclude that these plants have a beneficial effect on human health, both individually and as a component of food, due to their unique phytochemical profiles.